Molecular investigation reveals three hemotropic mycoplasmas in cats and three tick species in China - Shi, Hongfei; Li, Guoguang; Li, Dandan; Zhai, Hongyue; Ji, Shidong; Hu, Yun; Wang, Long; Yao, Lunguang (Frontiers in Veterinary Science, 2025)
To date, the primary hemoplasmas that infect cats include Mycoplasma haemofelis, ‘Candidatus Mycoplasma haemominutum’, and ‘Candidatus Mycoplasma turicensis’. In addition, other hemoplasmas Mycoplasma species have also been identified in cats. In central China, no infections or potential vectors with hemotropic mycoplasmas have been recorded in cats. To elucidate the prevalence of hemotropic mycoplasmas in both cats and parasitic ticks, this study investigated the occurrence of hemotropic mycoplasma infections in ticks and cats. A total of 78 blood samples were collected from both anemic and healthy cats, along with 284 ticks from the cats’ body surfaces and 356 ticks found in the surrounding environment. Following the morphological and molecular identification of ticks, all samples were screened for pathogens using PCR detection and sequence analysis. The results indicated the presence of 392 Haemaphysalis longicornis, 152 Rhipicephalus microplus, and 76 Rhipicephalus sanguineus sensu lato in cats and their surrounding environment. Molecular detection revealed the amplification of 156 ‘Ca. M. haemominutum’, 96 ‘Candidatus Mycoplasma haemobos’, 41 M. haemofelis, and 64 Rickettsia felis-positive amplicons from both cats and ticks. Notably, when comparing the infection rates of ‘Ca. M. haemobos’ in the environment group, no significant differences were observed in the infection rates among the three tick species from anemic or healthy cats (p > 0.05, α = 0.05). Furthermore, sequence analysis of ‘Ca. M. haemobos’ indicated two novel sequence types that were most closely related to an isolate from buffalo in China. In conclusion, in this study, in addition to ‘Ca. M. haemominutum’ and M. haemofelis, ‘Ca. M. haemobos’ was first detected in cats. ‘Ca. M. haemominutum’ appears to be associated with anemic syndrome in cats, while further research is needed to explore the relationship between ‘Ca. M. haemobos’ and clinical signs in felines. Additionally, these three hemotropic mycoplasmas were also found in three species of ticks, and transmission experiments are required to investigate the capacity of these ticks to transmit hemoplasmas Mycoplasma among animals.